Update Terbaru Kanker Seviks di Indonesia - Asrina Asrina; Nur Azmi Aliya; Ira Pasira; Nur Magfira; Alya Putri Salsadila; Nurul Fadillah; Yeti Mareta Undaryati (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Cervical cancer is a significant public health problem globally, including in Indonesia. This disease ranks fourth as the most common cancer in women in the world, with an estimated 604,000 new cases and 342,000 deaths in 2020. Analyzing the current condition of cervical cancer in Indonesia including prevalence, risk factors, impacts, prevention efforts, and treatment based on data to provide a comprehensive picture of the situation of cervical cancer in Indonesia. Cervical cancer is defined as a malignant tumor in the cervix that attacks the epithelial layer and has the potential to spread. Human Papilloma Virus (HPV) infection is the main cause of cervical cancer. In addition, several supporting risk factors include risky sexual behavior, long-term use of oral contraceptives, smoking habits, nutritional deficiencies (especially vitamins C, E, and folic acid), and poor personal hygiene. The Indonesian government has attempted to identify the disease early through the Visual Inspection of Acetic Acid (IVA) method used for early detection of cervical cancer in women aged 30 to 50 years. However, community participation in this program still needs to be improved sustainably. Treatment for cervical cancer can include surgery (eg cryosurgery, LEEP, hysterectomy), radiation, and chemotherapy. Cervical cancer remains a major health challenge in Indonesia. Improved education programs, participation in early detection of IVA, and strengthening of the health system as a whole are needed to effectively reduce morbidity and mortality caused by this disease.